Construire le rite comme un objet historique : pour un usage pragmatique de l’anthropologie en histoire religieuse du Québec - Hubert, Ollivier (Études d'histoire religieuse, 2001)
The revival of cultural history, and religious history is obviously concerned, is likely to incur an ill-considered rejection of some of the fundamental principles of social history: the will to include the totality of historical actors, the practice of a critical history, the question of the changing nature of the social link. Thus, the return to the "text", a promising means of renewal, carries the danger of a simple updating, or re-legitimization, of what the Power said of its doings. Hence, the work of a cultural historian implies a certain theoretical effort in order to invent new ways of linking discourses with the social practices in history. This is why a revival of the dialogue among disciplines is needed. It is this step which I followed, during a research project dealing with religious rites in 18th and 19th century Quebec, by setting up a link with a sister discipline: anthropology.